2018
DOI: 10.1017/s0022050718000359
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the 1896 Factory and Shops Act on the Labor Market of Victoria, Australia

Abstract: This article examines the effects of the Victorian Factory and Shops Act, the first minimum wage law in Australia. The Act differed from modern minimum wage laws in that it established Special Boards, which set trade-specific minimum wage schedules. We use trade-level data on average wages and employment by gender and age to examine the effects of minimum wages. Although the minimum wages were binding, we find that the effects on employment were modest, at best. We speculate that this was because the Special B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Wage rates are determined endogenously. Recently Seltzer and Borland () found that the rates fixed by Boards raised wage rates, as measured by the ratio of the Lowest Minimum Wage to the Average Wage in the sample, substantially compared to modern times but these fixed rates had little effect on employment in the covered trades. Most of the cases they observed occurred in the period of federation.…”
Section: Wage Protection In the Colonies 1850–1900mentioning
confidence: 99%
See 1 more Smart Citation
“…Wage rates are determined endogenously. Recently Seltzer and Borland () found that the rates fixed by Boards raised wage rates, as measured by the ratio of the Lowest Minimum Wage to the Average Wage in the sample, substantially compared to modern times but these fixed rates had little effect on employment in the covered trades. Most of the cases they observed occurred in the period of federation.…”
Section: Wage Protection In the Colonies 1850–1900mentioning
confidence: 99%
“…Wages Board legislation was established by South Australia in 1894 following closely the preceding Victorian legislation. In the colonial period, the number of workers covered by the Boards rose rapidly after 1898 (Seltzer & Borland, , figure 1).…”
Section: Wage Protection In the Colonies 1850–1900mentioning
confidence: 99%
“…Joe Sing, the Sydney manufacturer who complained of ‘being unable to dispose of my stock owing to the war’ stated that ‘there was no inspector who came along during the time I carried on’. Melbourne factory inspectors had some success in enforcing minimum wage law within the furniture industry, as Seltzer and Borland () have pointed out, and this is reflected in complaints made by European operators like Frederick Povey, noted earlier. A likely outcome of such success, however, at least according to Inspector Ellis in 1898, was the dismissal of old, slow, and sick Chinese workers.…”
Section: High Wagesmentioning
confidence: 99%